A Comprehensive Evaluation of a Drug Market Intervention Training Cohort in Roanoke, Virginia; Jacksonville, Florida; and Guntersville, Alabama, 2011-2013 - Saunders, Jessica ([Verlag nicht ermittelbar], 2016)
The Drug Market Intervention (DMI) has been identified as a promising practice for disrupting overt-drug markets, reducing the crime and disorder associated with drug sales, and improving police-community relations. Montgomery County, Maryland; Flint, Michigan; Guntersville, Alabama; Lake County, Indiana; Jacksonville, Florida; New Orleans, Louisiana; and Roanoke, Virginia applied for and received DMI training and technical assistance from Michigan State University in 2010 and 2011. This study followed the seven sites that were trained in the program to determine how the program was implemented, how the DMI affected the targeted drug market, whether the program affected crime and disorder, whether the program improved police-community relations, and how much the program cost.